Peran Rencana Usaha Penyediaan Tenaga Listrik (RUPTL) 2025-2034 sebagai Katalis Foreign Direct Investment (FDI) pada Sektor Pembangkit Listrik Tenaga Nuklir (PLTN) di Indonesia - Kanugraha, Septa Cahya (SENTRI: Jurnal Riset Ilmiah, 2025)
Indonesia is at an important crossroads in the national energy transition. Increasing electricity demand, limited fossil energy sources, and commitments to the Paris Agreement and the Net Zero Emission (NZE) 2060 target demand more ambitious energy diversification. In the 2025–2034 Electricity Supply Business Plan (RUPTL), for the first time the government includes a Nuclear Power Plant (NPP) with a capacity of 500 MW into the national energy mix. The inclusion of nuclear power plants in the RUPTL has strategic significance, not only in terms of stable electricity supply, but also as a public policy instrument that provides legal certainty and policy signals for foreign investors. This study confirms that the RUPTL has a dual function: to strengthen the bankability of projects through market certainty and long-term contracts, while providing the regulatory certainty needed to attract Foreign Direct Investment (FDI) in the nuclear sector. Through a comparative study with practices in the UAE, South Korea, Japan, and China, it was found that key factors for the success of nuclear power plants include regulatory independence, technology standardization, fiscal support, and public engagement. In Indonesia, the FDI opportunities for nuclear power plants are wide open, but they are still faced with disharmonious regulatory challenges, social resistance, and financing constraints. Therefore, legal harmonization strategies, transparent public communication, and innovative financing schemes are the keys to strengthening the attractiveness of foreign investment in the nuclear power plant sector.